Media Pembelajaran Huruf Hijaiyah untuk Siswa Sekolah Dasar berbasis Augmented Reality - Novandaru Achnivandra Dwi Fortuna; Hardika Dwi Hermawan (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The ability of grade 1 students of SD N Ponowaren 02 to recognize and memorize hijaiyah letters that are still lacking needs to be improved. Today's technology can be utilized as a learning media by using smartphones. Especially in the world of education, the use of this technology can facilitate both teachers and students in an innovative, creative, and educational learning process. The purpose of this research is to develop teaching materials that encourage and increase children's interest in learning Hijaiyah letters by utilizing augmented reality technology. In this study using the Research and Development approach method. The method is used to produce certain products and test the effectiveness of the product, then for the product development model using the Multimedia Development Life Cycle, which includes concept, design, material collection, manufacturing process, testing, and product distribution. Observation and questionnaires are used for the data collection process. This research shows how augmented reality technology combined with educational games can improve children's learning efficiency in learning hijiayah letters. Based on the research of learning media game Bijaya (Belajar huruf hijaiyah) shows that the feasibility of media obtains results above 90%. Based on the Likert scale test criteria, this shows that the Bijaya application learning media is very feasible to be developed and utilized.